Are EU Candidate Countries Ready for the Single Market? Comparing Performance with an EU Benchmark - Jan De Loecker (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2002)
The process of the East-West integration has come to a point that enlargement appears inevitable. But are these countries really ready to join the EU in tfirms of competitive perfirmance? Firstly, we construct a virtual best practice production frontier for firms active in a European Union member state (EU) and firms in Central and East European (CEE) countries. By means of this common benchmark, we make inferences about the relative technical efficiency of firms in candidate countries. We show that technical efficiency is higher in the EU, however, firms in CEE countries are converging towards the EU average. We show that efficiency is not only different between countries, but even within countries. The latter suggests the need to look at industry-level technical efficiency. Secondly, we combine two existing techniques to develop a methodology to estimate firm level total factor productivity (TFP) change, decomposed into technical change, technical effiency change and a scale component. It is mainly technical change that drives the change in TFP, i.e. technological progress. firms in EU candidate countries are reallocating resources under decreasing returns to scale, leading to an increase in TFP. We suggest interpreting efficiency estimates as measures of firm heterogeneity.
Keywords: P2; P5; L6; C33; 330; EU enlargement; stochastic frontier; technical efficiency; total factor productivity.; Wirtschaftliche Anpassung; EU-Erweiterung; Produktivität; Technische Effizienz; Benchmarking; Belgien; Polen; Tschechische Republik; EU-Beitrittskriterien